PRAKTIK PAYLATER DALAM PERSPEKTIF ISLAM: ANALISIS TERHADAP UNSUR RIBA, GHARAR, DAN ISRAF PADA TRANSAKSI DIGITAL - Abd Ghafur; Muhammad Imron; Muhammad Saiful Rizal; Moh.Fahmi Idris (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The development of PayLater services within the financial technology (fintech) ecosystem has provided easier access to financing for consumers; however, it has also raised various concerns from the perspective of Islamic business ethics. This study aims to analyze PayLater practices based on Sharia principles, particularly concerning the elements of riba, gharar, and israf. The research employs a qualitative library research method with a descriptive-analytical approach. The findings indicate that conventional PayLater practices potentially involve elements of riba through interest charges and late-payment penalties that generate profits for service providers. Furthermore, elements of gharar arise from unclear contractual arrangements, information asymmetry, and a lack of transparency regarding transaction costs and risks. From the consumer behavior perspective, the ease of access provided by PayLater contributes to increased consumptive behavior and israf, which contradict Islamic principles of wealth management.